LEADERSHIP IN THE DIGITAL ERA : ANALYZING THE IMPACT OF TECHNOLOGY ON LEADERSHIP STYLE AND ITS EFFECTIVENESS ON FINTECHS IN LAGOS, NIGERIA. - Fadeyi, Maria (2025)
With the fintech industry at the forefront of digital innovation, leaders are increasingly required to navigate rapid technological advancements, changing workforce dynamics, and intense market competition. This study examines how digital technology influences leadership styles and effectiveness within fintech firms in Lagos, Nigeria. Guided by Transformational Leadership Theory, Technology Acceptance Model, and Adaptive Leadership Theory, this study explored the extent to which tools such as digital collaboration platforms, data analytics, and artificial intelligence transform leadership behaviors. Using a cross-sectional survey with quantitative techniques, the study finds that technology has a positive relationship with leadership styles, and strongly improves decision-making, team collaboration, and operational efficiency. The study also reveals challenges (such as poor internet and unreliable infrastructure, financial constraints, and cybersecurity threats) hindering effective technology adoption. Emotional intelligence, agility, effective communication, and cyber awareness are key skills found to be critical to technology adoption. The findings offer practical insights for fintech leaders on how to proactively create an organisational culture that supports the effective adoption of digital tools. It also underscores the need for leaders to develop digital competencies, promote innovation and agility, and align tools with strategic goals.